2017
DOI: 10.3122/jabfm.2017.06.170064
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Opioid Prescriptions to Physical Therapy Referral and Participation for Medicaid Patients with New-Onset Low Back Pain

Abstract: Introduction: Physical therapy (PT) early in the management of low back pain (LBP) is associated with reductions in subsequent health care utilization and LBP-related costs. The objectives of this study were to 1) Examine differences among newly consulting patients with LBP who received a PT referral and those who did not, 2) examine differences between patients who participated in PT to those who did not, and 3) compare the impact of a PT referral and PT participation on LBP-related health care utilization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 30 publications
2
29
0
1
Order By: Relevance
“…Fritz et al found that early PT was associated with decreased opioid prescriptions,32 and a review by Ojha et al noted that early PT as treatment for musculoskeletal disorders was associated with decreased frequency of opioid prescriptions, although this was based on a limited number of outcomes 33. Thackerary et al also suggested that the odds of receiving an opioid prescription among Medicaid beneficiaries were reduced for those who had a PT consult, as compared with those who did not 34. While these studies did not measure the odds of opioid use among patients who initially saw physical therapists compared with other initial providers, our results are consistent with previously published reports that PT is associated with lower odds of opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Fritz et al found that early PT was associated with decreased opioid prescriptions,32 and a review by Ojha et al noted that early PT as treatment for musculoskeletal disorders was associated with decreased frequency of opioid prescriptions, although this was based on a limited number of outcomes 33. Thackerary et al also suggested that the odds of receiving an opioid prescription among Medicaid beneficiaries were reduced for those who had a PT consult, as compared with those who did not 34. While these studies did not measure the odds of opioid use among patients who initially saw physical therapists compared with other initial providers, our results are consistent with previously published reports that PT is associated with lower odds of opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to derive a CPR to identify patients who might be more likely to become chronic users of prescription opioids after orthopedic hip surgery. While other studies have utilized prescription data to define chronic opioid use (Fritz et al 2018 ; Sites et al 2018 ; Thackeray et al 2017 ), this study is the first to develop a clinical prediction rule based on opioid prescription patterns validated from pharmacy data in claims records. The focus of our investigation was to better understand variables that may improve clinical decision-making related to managing patients that are taking opioids after surgery and at the same time generate hypotheses for future trials.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with a number of claims-based studies indicating lower opioid prescribing in those patients engaging in PT. [35,36] However, these studies focus on outpatients, in whom our population of patients in the ED may significantly differ, both in terms of urgency of encounter and acute pain score. It may also be the case that PT has a more protective effect against opioid prescribing long-term, and is less effective as an opioid substitution therapy acutely at the point of ED discharge Further research may clarify the comparable rates of outpatient opioid prescribing between those who receive ED-PT and those who do not.…”
Section: Plos Onementioning
confidence: 99%